A Tandem Approach towards Diastereoselective Synthesis of Quinoline C‐3 Tethered γ‐Lactones. Issue 2 (9th January 2018) - Kumar, Vipin; Chaudhary, Sandeep; Mathur, Manas; Swami, Ajit K.; Malakar, Chandi C.; Singh, Virender
Abstract: A convenient approach has been developed for the facile synthesis of novel quinoline and α‐methylene γ‐butyrolactones based molecular hybrids. The tandem synthesis of quinoline C‐3 tethered lactone derivatives was achieved via indium‐mediated Barbier Type allylation followed by in situ intramolecular lactonisation approach. Abstract : Barbier Type Allylation: A one‐pot tandem approach has been devised for the facile synthesis of novel quinoline and α‐methylene γ‐butyrolactones based molecular hybrids.